Spatiotemporal variations of asthma admission rates and their relationship with environmental factors in Guangxi, China - Rui Ma; Lizhong Liang; Yunfeng Kong; Mingyang Chen; Shiyan Zhai; Hongquan Song; Yane Hou; Guangli Zhang (BMJ Open)
Objective The study aimed to determine if and how environmental factors correlated with asthma admission rates in geographically different parts of Guangxi province in China.Setting Guangxi, China.Participants This study was done among 7804 asthma patients.Primary and secondary outcome measures Spearman correlation coefficient was used to estimate correlation between environmental factors and asthma hospitalisation rates in multiple regions. Generalised additive model (GAM) with Poisson regression was used to estimate effects of environmental factors on asthma hospitalisation rates in 14 regions of Guangxi.Results The strongest effect of carbon monoxide (CO) was found on lag1 in Hechi, and every 10 µg/m3 increase of CO caused an increase of 25.6% in asthma hospitalisation rate (RR 1.26, 95% CI 1.02 to 1.55). According to the correlation analysis, asthma hospitalisations were related to the daily temperature, daily range of temperature, CO, nitrogen dioxide (NO2) and particulate matter (PM2.5) in multiple regions. According to the result of GAM, the adjusted R2 was high in Beihai and Nanning, with values of 0.29 and 0.21, which means that environmental factors are powerful in explaining changes of asthma hospitalisation rates in Beihai and Nanning.Conclusion Asthma hospitalisation rate was significantly and more strongly associated with CO than with NO2, SO2 or PM2.5 in Guangxi. The risk factors of asthma exacerbations were not consistent in different regions, indicating that targeted measures should differ between regions.